Preface: Recent Developments in Taxonomy and Biodiversity of Symbiotic Copepoda (Crustacea)—A Volume in Celebration of the Career of Prof. Il-Hoi Kim - Huys, Rony (Zootaxa, 2016)
Symbiosis is one of the most successful modes of life displayed by aquatic organisms, as measured by the number of times it evolved and how many symbiotic species are presently in existence. Among the Crustacea copepods utilize an extraordinary range of hosts, occurring on virtually every phylum of marine macroinvertebrates and, jointly with the monogeneans, are the most speciose group of metazoan ectoparasites of marine fishes (Rhode 2005). Several species have a major impact on global finfish and shellfish aquaculture, causing significant effects on farm production, economic viability and sustainability (Shinn et al. 2015). Parasitism by copepods on other metazoans has evolved independently numerous times in the evolutionary history of animal life on Earth and has led to an exceptional diversity in morphologies, physiologies, life-strategies and habitat preferences of its members. Reflecting the diversity of hosts, copepods show an amazing variety of adaptations which secure infection of and survival on the hosts. Since the first descriptions of parasitic copepods occurring on fish by Linnaeus (1758) and the first report of a copepod utilizing an invertebrate host by Say (1818) (Clausidium caudatum (Say, 1818)) the number of described symbiotic copepods has seen a steady increase over a 200-yr period, culminating in a total of 5,306 valid species recognized today. About 38% of all described copepod species utilize either vertebrate (2,450 spp.) or invertebrate hosts (2,856 spp.), however, many host groups have not been thoroughly examined, and for this reason even approximate estimates of true species numbers are futile. Plotting the proposal of new species by decade (Fig. 1) shows a sharp rise since 1950 with 67% of the species having been described in the preceding 65 years. This period of exceptionally rapid progress can be attributed to a number of highly prolific investigators such as Arthur Humes, Il-Hoi Kim, Ju-shey Ho and Jan Stock who, single-handedly or in collaboration with other authors, described 698, 356, 290 and 246 species, respectively. Historically, the number of described copepod species parasitizing fish typically outnumbered those known to be associated with invertebrates. Only during the mid-1970s the species curves of both categories converged and during the last 30 years the discovery of new species associated with invertebrate hosts appears to progress more rapidly. Despite a significant drop in the number of specialists working on symbiotic copepods the steady addition of new taxa shows that the dynamism of their taxonomy is clearly set to continue.